IN SILICO IDENTIFICATION TESTING OF TRITERPENE SAPONINES ON CENTELLA ASIATICA ON INHIBITOR RENIN ACTIVITY ANTIHYPERTENSIVE - ASTIANI, RANGKI; SADIKIN, MOHAMAD; EFF, APRILITA RINA YANTI; FIRDAYANI; SUYATNA, FRANCISCUS D. (International Journal of Applied Pharmaceutics, 2022)
The renin-angiotensin-aldosterone system (RAAS) has an essential role in the occurrence of hypertension. Two drugs that act on SRAA are ACE Inhibitor and ARB. ACE inhibitor and ARB are two antihypertensive drugs that act on RAAS. However, both drugs are not fully effective because they produce incomplete suppression of RAAS. The therapeutic potential of the two drugs is limited, so it is necessary to find out other drugs that are more effective in inhibiting the RAAS system. Renin-inhibitors are evolving as options that can inhibit at the highest levels in RAAS. Discontinuation of renin inhibitor therapy does not cause rebound hypertension as in ACEIs and ARBs. The search for natural renin inhibitors began to be carried out as an alternative to aliskiren. Renin-inhibitors derived from natural ingredients generally come from the class of saponin compounds or polyphenol compounds. One of Indonesia's native plants that contain saponins and polyphenols is Centella asiatica. Thus, research on the antihypertensive potential of these plants was carried out. It is expected that the Centella asiatica plant has a renin inhibitor effect as a blood pressure-lowering drug derived from herbs but has the same effect as aliskiren. The research method was carried out in silico to test the activity of compounds that have potential as antihypertensives in the Centella asiatica plant. The method used is molecular docking, with the docking software used being Molegro Virtual Docker (MVD) 6.0. The results showed that madecasoside and asiaticoside from the Centella asiatica plant have intense renin inhibitor activity, with a mean re-rank score of-105.27 and-93.67, respectively. The conclusion is that madecasoside has similarities with aliskiren with a re-rank value of-105.27. The smallest re-rank value indicates the similarity and strong protein binding between the tested ligand compound and the comparison protein.